STRATEGI PENGEMBANGAN OBJEK WISATA DALAM UPAYA PENINGKATAN KUNJUNGAN - Nuh Saneraro Fakdawer; Yoseb Boari; Shofia Yunus Manginte; Maikel Walilo (Realism: Law Review, 2023)
This research explores the tourism potential of Lake Love in Jayapura, Papua Province, with an emphasis on the crucial role of natural tourism in the country's tourism industry. While the uniqueness of this destination attracts interest, its development represents several challenges that require special attention. The first main obstacle is the need for environmental maintenance, because the beauty of Lake Cinta is very dependent on the preservation of the surrounding environment, where a lack of maintenance can reduce its tourist attraction. The second barrier covers local economic and development potential, requiring effective management to maximize economic benefits for local communities, including the development of tourism infrastructure. The lack of tourism promotion is an additional obstacle, requiring greater efforts to increase the visibility of Jayapura City as an attractive destination in Indonesia, which has the potential to increase tourist visits. This research aims to design a strategy for developing Love Lake tourism in Jayapura and identify obstacles and challenges in developing Love Lake tourism in Jayapura. The method used is a descriptive analysis approach. Research results show that 1). environmental preservation and cleanliness of tourist areas. 2). infrastructure development is needed, 3). promotion and marketing, 4). strategies involving the development of diverse tourism activities, 5). training and education for tour guides and local residents, 6). active collaboration with local communities, 7). Investment diversification, and 8). feedback and evaluation from visitors.